Indonesian perceptions on online learning amidst COVID-19: a Twitter sentiment analysis - Muhammad Abduh; Muhammad Hamka; Tukiran Taniredja; Almuntaqo Zainuddin; Wahdan Najib Habiby (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The objective of this research is to uncover Indonesians' perceptions of online learning during the COVID-19 pandemic by determining the polarity of language texts (positive, neutral, or negative) compiled from Twitter. The data required to reveal the Indonesian people's opinion on online learning during the COVID-19 pandemic is a tweet on Twitter with the hashtag #Pembelajaran daring (Online learning); #Pembelajaran jarak jauh (distance learning); #Belajar dari rumah (learning from home); #Belajar di rumah (learning in the home) (learning at home). The time frame for collecting these tweets is March 2020 to November 2021. The data was then analyzed using lexicon analysis and analytical tools that used Part of Speech Tagging. According to the results, 77.58% of the tweets are positive, 17.97% are negative, and the remainder are neutral. People prefer to refer to learning support, teachers, schools, education, students, and distance learning. Distance learning is the most positively received category among online learning. However, learning support is the most widely discussed topic among the general public. The overwhelming positive sentiment across all categories suggests that the majority of Indonesians have high hopes for online learning during the pandemic.